2004
DOI: 10.2320/matertrans.45.2364
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction Equilibria of FeCl<SUB>3</SUB> from Hydrochloric Acid Solution with Alamine336

Abstract: We have conducted solvent extraction experiments of FeCl 3 in HCl solution with Alamine336 as an extractant. Solvent extraction reaction depended on the ratio of initial concentration of Alamine336 to FeCl 3 . When the concentration of Alamine336 was in excess to that of FeCl 3 , the extractant reacted as a dimer. When the initial concentration ratio of Alamine336 to FeCl 3 was below three, ferric chloride was extracted by monomeric extractant. The equilibrium constants of solvent extraction were determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13] TBP, TOPO, and DOS have been widely used in the separation of base metals together with PGMs 13,14) and in the refining of precious metals. 15,16) The existence form of PGMs and availability of certain type of metal species are highly dependent on the acidity and chloride concentration in the aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] TBP, TOPO, and DOS have been widely used in the separation of base metals together with PGMs 13,14) and in the refining of precious metals. 15,16) The existence form of PGMs and availability of certain type of metal species are highly dependent on the acidity and chloride concentration in the aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 Alamine336 (Tertiary amine, R3N, R = CH3(CH2)7) is an anionic extractant and is extensively used in the solvent extraction of various metal ions. 3,[5][6][7] Sayar et al reported the data on the solvent extraction of zinc by Alamine336 from HCl solution up to 10 M. 3 They proposed the following equation to simulate the solvent extraction behavior of zinc in their system. …”
Section: Introductionmentioning
confidence: 99%
“…The hydrochloric acid concentration in feed liquor has an important influence on iron extraction [16]. It has been reported that FeCl 3 in the presence of HCl contributes to form HFeCl 4 which could then combine with TBP in the extracted complex and facilitates extraction reaction [9].…”
Section: Effect Of Hcl Concentrationmentioning
confidence: 99%